Bulk Production of Baculovirus Expressed Stable Virus Like Particles of FMD Virus: Concentration, Purification and Semi Quantification - Adwitiya, Das; Chandan S, Tilak; Dubey, Samriddhi; Katrapati, Lakshmikanth; Dhakarwal, Pankaj; Chaudhuri, Pallab; Paramasivam, Saravanan (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The Virus-like Particles (VLPs) have the same epitopes as the native virus offering a great alternative to conventional vaccines due to the lack of genome along with eliciting both arms of immunity. The thermostabilized Foot and Mouth Disease (FMD) VLP-based antigen with inherent DIVA compatibility requires minimum biosafety and cold chain maintenance for the production and transit process. It can potentially replace conventional virus handling during antigen production for prophylactic as well as diagnostic use. Preparation of baculovirus expressed VLPs for vaccine formulation can be achieved by bulk production of VLPs in insect cell culture like Tn5 and Sf21 grown in a shaker incubator at standard conditions followed by concentration of the harvested cell culture supernatant and purification by discontinuous sucrose density gradient with nine different gradients giving high yield. We standardized the bulk production of VLPs in a refrigerated shaker incubator maintaining a temperature of 26°C, concentrated and purified it in simplified sucrose density gradient ultracentrifugation, that could prove to serve as a potential vaccine candidate attributing to its thermostable properties.